Antecedent Organizational Commitment Approach that Affects Employee Engagement - Jumawan; Andrianto Widjaja (International Journal of Business and Applied Economics, 2023)
This study aims to find out what factors can support the employee engagement in a corporate organization, this study uses a literature review of several articles related to dependent and independent, in this study does not use a questionnaire distribution involving respondents, the findings of this study are all variables independent variables significantly influence the dependent variable, so employee engagement is successful if there is support or influence from the independent variables and intervening variable. For the future, research can be developed with the variables in this scientific article with research methods, references or objects used.